Asociación entre síndrome de intestino irritable y la ansiedad - depresión en pacientes atendidos en el Hospital Regional Docente de Trujillo - Mariños Llajaruna, Humberto Rafael (2020)
ABSTRACT A correlational study was carried out using a sample of 195 medical records of patients diagnosed with Irritable Bowel Syndrome (IBS) at Regional Hospital of Trujillo (RHT) – Peru between January 2014 and December 2016, the aim of the study was to determine if there is a relation between the irritable bowel syndrome and anxiety or depression in adult outpatients. 93.3% of the patients presented anxiety with a prevalence of moderate anxiety followed by mild anxiety, hence there is a relation between the level of anxiety and the presence of IBS (x2= 8,5557 p= 0,0358). On the other hand, 88,7% of the patients presented depression with a prevalence of mild depression followed by moderate depression, thus, there is also a relation between the level of depression and the presence of IBS (x2 = 9,1396 p = 0,0275). In conclusion, there is a relation between the irritable bowel syndrome and anxiety as well as depression in adult patients.